Pasty biological tissue adhesive capable of being coated as well as preparation method and application of pasty biological tissue adhesive

By using lipoic acid, phenol structural compounds and quaternary ammonium salt compounds under vacuum heating polymerization conditions, the problems of low bond strength and complex preparation process of existing biological tissue adhesives are solved, and the bonding effect of high strength, stability and biocompatible is achieved.

CN119896763APending Publication Date: 2025-04-29HARBIN INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510091387.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing biological tissue adhesives have problems such as low bond strength, complex preparation process, single function, poor durability and high preparation cost.

Method used

Lipoic acid or its derivatives, phenol structural compounds and quaternary ammonium salt compounds are used as raw materials to prepare paste-like biological tissue adhesives under vacuum heating polymerization conditions, and the adhesive properties are optimized by adjusting the molar ratio and heating time.

Benefits of technology

The prepared adhesive has high strength, stability and biocompatible, and can effectively bond a variety of tissues and polymer materials. It has stable bonding properties and does not decay with time, and has good room temperature storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896763A_ABST
    Figure CN119896763A_ABST
Patent Text Reader

Abstract

The invention discloses a pasty biological tissue adhesive capable of being coated as well as a preparation method and application thereof, and belongs to the technical field of biological tissue adhesives and preparation thereof. The invention solves the problems of low adhesive property, complex preparation process and the like of the existing tissue adhesive. A phenol structure compound and a quaternary ammonium salt compound are introduced in the heating polymerization process of lipoic acid, and the pasty biological tissue adhesive which can be directly used for coating is prepared. The adhesive is high in adhesion performance, high in stability, good in biocompatibility and free of tissue toxicity, can be implanted into a body or attached to a body surface wound, and has the effects of isolating the wound, adhering and fixing tissue, helping the wound to heal and repair and the like. And the adhesive property cannot be attenuated along with the change of time, the adhesive has good room-temperature storage stability, and long-time effective adhesion to tissues can be realized. In addition, the preparation process provided by the invention is simple and environment-friendly, the synthesis steps are simple, the raw materials are cheap and easily available, and long-term stable storage can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coatable paste-like biological tissue adhesive and a preparation method and application thereof, belonging to the technical field of biological tissue adhesive and preparation thereof. Background Art

[0002] Biological tissue adhesives have emerged as promising alternatives to standard wound closure devices, including sutures, staples, clips, and strips, as they are relatively easy and quick to use, with minimal tissue damage, rapid hemostasis, and the ability to reduce the risk of infection. A variety of synthetic and natural materials have been used as bioadhesives. These materials have a wide range of applications in a variety of biomedical fields, from simple wound sealing to controlled drug delivery, tissue regeneration, and non-invasive treatments.

[0003] Despite significant progress and achievements, several major challenges remain: ① The primary problem with current biological tissue adhesives is their low bonding strength, which makes them an unsuitable substitute for sutures, especially when the tissue is moist and subjected to repeated loads; ② The adhesives have a single function and cannot provide more auxiliary therapeutic effects while achieving wound adhesion; ③ The adhesives have poor durability, and it is urgent to improve the elasticity, toughness and deformation resistance of the adhesive body while ensuring high-strength interfacial adhesion, so as to achieve strong adhesion in a highly dynamic physiological environment; ④ The adhesive preparation cost is very high, the synthesis process is complex, the technology is time-consuming and may inevitably lead to errors, which is difficult to achieve. To achieve mass production and application (Sci. Transl. Med., 2013, 5, 205ec161; J. Biomed. Mater. Res. B, 2016, 104, 626-639; Adv. Healthc. Mater., 2019, 8, 1801568; Sci. Adv., 2023, 9, eadh4327; Biomaterials, 2023, 301, 122239; Adv. Mater., 2024, 2401745; Adv. Mater., 2024, 2404811).

[0004] Therefore, it is very important and meaningful to develop a biological tissue adhesive with high-strength bonding performance and simple preparation process. Summary of the invention

[0005] In order to solve the problems of low adhesive performance and complicated preparation process of existing biological tissue adhesives, the present invention provides a coatable paste-like biological tissue adhesive and a preparation method and application thereof.

[0006] The technical solution of the present invention:

[0007] One of the purposes of the present invention is to provide a paste-like biological tissue adhesive which can be coated. The adhesive is obtained by vacuum heating polymerization in the presence of a solvent using lipoic acid or lipoic acid derivatives, phenol structure compounds and quaternary ammonium salt compounds as raw materials.

[0008] It is further defined that the molar ratio of lipoic acid or lipoic acid derivatives, phenol structure compounds and quaternary ammonium salt compounds is 1:(0-10):(1-20).

[0009] It is further defined that the lipoic acid derivative is ethyl lipoate and / or L-carnitine lipoate.

[0010] It is further defined that the phenol structure compound is a mixture of one or more of caffeic acid, dopamine, levodopa, dihydrocaffeic acid, tannic acid, tea polyphenols, and gallic acid.

[0011] It is further defined that the quaternary ammonium salt compound is a mixture of one or more of L-carnitine, betaine, choline chloride, glycerophosphocholine, choline benzenesulfonate, choline citrate, and choline dihydrogen citrate.

[0012] It is further defined that the solvent is anhydrous ethanol and / or deionized water.

[0013] It is further defined that the mass volume ratio of the total mass of the raw materials to the solvent is (0.5-5.0) g:1 mL.

[0014] The second object of the present invention is to provide a method for preparing the above-mentioned coatable paste-like biological tissue adhesive, which specifically comprises: dissolving lipoic acid or lipoic acid derivatives, phenol structure compounds and quaternary ammonium salt compounds in a solvent, placing them in a vacuum oven for heating and polymerization treatment, and obtaining a coatable paste-like biological tissue adhesive.

[0015] It is further defined that the heating polymerization temperature is 70° C. and the time is 1 to 48 hours.

[0016] The third object of the present invention is to provide an application of the above-mentioned paste-like biological tissue adhesive, and the specific application method is to directly apply the adhesive to the surface of the adherend.

[0017] Beneficial effects of the present invention:

[0018] (1) The present invention introduces phenol structure compounds and quaternary ammonium salt compounds during the heating polymerization of lipoic acid to prepare a paste-like biological tissue adhesive that can be directly used for coating. The adhesive has strong bonding performance, strong stability, good biocompatibility, and no tissue toxicity. It can be implanted in the body or attached to the wound on the surface of the body to isolate the wound, bond and fix the tissue, and help the wound heal and repair. In addition, the bonding performance of the biological tissue adhesive will not decay with the change of time, has good room temperature storage stability, and can achieve long-term effective bonding of tissues; it has high-strength bonding performance to a variety of tissues and a variety of polymer materials. In addition, the preparation process provided by the present invention is simple and environmentally friendly, the synthesis steps are simple, the raw materials are cheap and easy to obtain, and it can be stored stably for a long time.

[0019] (2) The present invention increases the wetting ability of the adhesive to the tissue under the solvent-free condition by adding the hydrophilic quaternary ammonium salt compound in the thioctic acid heating polymerization process, realizes that it can be directly and evenly coated on the tissue surface, and the solvent-free adhesive is more conducive to transportation and preservation. In addition, in the preparation process of the adhesive, the difference in the stacking form of the polymer molecules of the thioctic acid-phenol structure compound and the hydrophilic quaternary ammonium salt compound of small molecules under the action of solvent is utilized, and the self-assembly microstructure of different stacking forms is realized, thereby affecting the adhesive property of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a photograph of the reaction solution for preparing the adhesive in Examples 4 to 9;

[0021] Figure 2 Scanning electron microscope images of the adhesives prepared in Examples 4 to 8 (at different magnifications);

[0022] Figure 3 These are photographs of the adhesives prepared in Examples 16 and 20. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0025] Example 1

[0026] 0.64 g of lipoic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0027] Example 2

[0028] 0.51 g of lipoic acid, 0.11 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0029] Example 3

[0030] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0031] Example 4

[0032] 0.13 g of lipoic acid, 0.45 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0033] Example 5

[0034] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved with anhydrous ethanol to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0035] Example 6

[0036] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 10:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0037] Example 7

[0038] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 5:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0039] Example 8

[0040] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0041] Example 9

[0042] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:2 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0043] Example 10

[0044] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 3 h to obtain an adhesive.

[0045] Embodiment 11

[0046] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 6 h to obtain an adhesive.

[0047] Example 12

[0048] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 18 h to obtain an adhesive.

[0049] Example 13

[0050] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70° C. for 24 h to obtain an adhesive.

[0051] Embodiment 14

[0052] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 0.80 g / mL, which was heated in a vacuum oven at 70°C for 36 h to obtain an adhesive.

[0053] Embodiment 15

[0054] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.00 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0055] Example 16

[0056] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0057] Embodiment 17

[0058] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 2.00 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0059] Embodiment 18

[0060] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 2.50 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0061] Embodiment 19

[0062] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.5 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 3.00 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0063] Embodiment 20

[0064] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.36 g of betaine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0065] Embodiment 21

[0066] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.43 g of choline chloride were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0067] Embodiment 22

[0068] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.80 g of glycerophosphocholine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, which was heated in a vacuum oven at 70°C for 12 h to obtain an adhesive.

[0069] Embodiment 23

[0070] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.86 g of choline toluenesulfonate were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0071] Embodiment 24

[0072] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.52 g of choline citrate were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, which was heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0073] Embodiment 25

[0074] 0.32 g of lipoic acid, 0.28 g of caffeic acid and 0.92 g of choline dihydrogen citrate were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0075] Embodiment 26

[0076] 0.32 g of lipoic acid, 0.30 g of ferulic acid and 0.50 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0077] Embodiment 27

[0078] 0.32 g of lipoic acid, 0.28 g of dihydrocaffeic acid and 0.50 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, and heated in a vacuum oven at 70° C. for 12 h to obtain an adhesive.

[0079] Embodiment 28

[0080] 0.32 g of lipoic acid, 0.28 g of dihydrocaffeic acid and 0.36 g of betaine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, and heated at 70° C. in a vacuum oven for 12 h to obtain an adhesive.

[0081] Embodiment 29

[0082] 0.57 g of L-carnitine lipoate, 0.28 g of dihydrocaffeic acid and 0.50 g of L-carnitine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, and heated at 70° C. in a vacuum oven for 12 h to obtain an adhesive.

[0083] Embodiment 30

[0084] 0.57 g of L-carnitine lipoate, 0.28 g of dihydrocaffeic acid and 0.36 g of betaine were placed in a round-bottom flask and dissolved in a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a reaction solution with an initial concentration of 1.50 g / mL, and heated at 70° C. in a vacuum oven for 12 h to obtain an adhesive.

[0085] Effect example

[0086] Adhesion performance test:

[0087] Fresh pig skin, pork, aorta, heart, liver, kidney, stomach, bladder and large intestine and other biological tissues were purchased in the supermarket, and the adhesive prepared in each embodiment was applied to two tissue surfaces and slightly pressed. Then, a universal mechanical testing machine was used to test the bonding strength and bonding toughness of the adhesive on different tissue surfaces, with 3 to 5 samples in each group, and the average value was taken as the final result.

[0088] The bonding strength test method is a single lap shear test mode. During the test, the sample is stretched in two opposite directions parallel to the bonding surface at a tensile rate of 50 mm / min, and the peak value of the stress F (N) at the moment of pulling apart is tested. The stress per unit bonding area is calculated according to formula (1), which is the bonding strength of the sample.

[0089] T=1000F / S (1)

[0090] Where F is the peak stress at the moment of pulling apart, in N; S is the bonding area, in mm 2 ; T is the lap shear strength, unit is kPa.

[0091] The bonding toughness test method is a T-type peel test mode. During the test, the sample is stretched in two opposite directions perpendicular to the bonding surface at a tensile rate of 50 mm / min. After the applied force is stable, the peel force F (N) is recorded and the bonding toughness of the sample is calculated according to formula (2).

[0092] τ = 2F / L (2)

[0093] Where F is the peel force after stabilization, in N; L is the width of the bonding surface, in m; τ is the bonding toughness, in J / m 2 .

[0094] The test results are shown in the following table:

[0095] Table 1 Adhesion strength of adhesives to pigskin in Examples 1-28

[0096]

[0097]

[0098] As shown in Table 1 above, the molar ratio of lipoic acid to phenol structure compound has a great influence on the bonding performance, and the bonding performance is best when the ratio is 1:1, because the quaternary ammonium salt substances mainly interact with the phenol structure compound to enhance its hydrophilicity. When the hydrophilicity is too strong, the adhesive will dissolve and be unfavorable for bonding, while when the hydrophilicity is too weak, the adhesive will be inconvenient to apply and will also be unfavorable for bonding.

[0099] Further comparison of the bonding results of the adhesives prepared in various examples on pig skin shows that the solvent composition has a certain influence on the bonding performance of the adhesive. The bonding performance is strongest when the solvent is anhydrous ethanol and deionized water with a volume ratio of 2:1. This is because the self-assembly behavior of the adhesive is different under different solvents. The higher the water content, the more complex the self-assembly degree of the adhesive molecules. For details, see Figure 2 The higher the water content, the more complex the stacking form of small molecule hydrophilic compounds and lipoic acid-caffeic acid polymer molecules under the action of solvent, resulting in differences in the microscopic morphology of the adhesive.

[0100] It can also be concluded from Table 1 that the heating time will affect the bonding performance of the adhesive within a certain range. This is because if the heating time is too short, the chain segments of the polymer in the adhesive will be shorter, which is not conducive to bonding.

[0101] Table 2 Adhesion performance of the adhesive in Example 16 to pork, aorta, heart, stomach, bladder and large intestine

[0102]

[0103] Table 3 Adhesion performance of the adhesive in Example 20 to pork, aorta, heart, stomach, bladder and large intestine

[0104]

[0105] Table 4 Adhesion performance of the adhesive in Example 16 to pigskin after storage at room temperature for different time periods

[0106]

[0107]

[0108] Table 5 Adhesion performance of the adhesive in Example 20 to pigskin after storage at room temperature for different time periods

[0109]

[0110] Table 6 Adhesion performance of the adhesive in Example 16 for different time periods in simulated in vivo environment to pig skin

[0111]

[0112] Table 7 Adhesion performance of the adhesive in Example 20 for different time periods in simulated in vivo environment to pig skin

[0113]

[0114] Table 8 Adhesion performance of adhesives in Example 16 between different polymer materials and pigskin

[0115]

[0116] Table 9 Adhesion performance of adhesives in Example 20 between different polymer materials and pigskin

[0117]

[0118] Table 10 Moisture retention performance of the adhesive in Example 16 and Example 20 on pig skin (water loss rate / %)

[0119]

[0120] It can be seen from Tables 2 to 10 above that the adhesive prepared by the present invention has high-strength adhesion to a variety of biological tissues and a variety of polymer materials, and the adhesion performance does not decay with time, and has good room temperature storage stability; and has adhesion stability, and can achieve long-term effective adhesion to tissues; in addition, it also has good moisturizing properties.

[0121] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A paste-like biological tissue adhesive, characterized in that: The adhesive is prepared by using thioctic acid or thioctic acid derivatives, phenol structure compounds and quaternary ammonium salt compounds as raw materials and is obtained by vacuum heating and polymerization in the presence of a solvent.

2. The adhesive according to claim 1, characterized in that The molar ratio of lipoic acid or lipoic acid derivatives, phenol structure compounds and quaternary ammonium salt compounds is 1: (0-10): (1-20).

3. The adhesive according to claim 1, characterized in that The lipoic acid derivative is ethyl lipoate and / or L-carnitine lipoate.

4. The adhesive according to claim 1, characterized in that The phenol structure compound is a mixture of one or more of caffeic acid, dopamine, levodopa, dihydrocaffeic acid, tannic acid, tea polyphenols and gallic acid.

5. The adhesive according to claim 1, characterized in that The quaternary ammonium salt compound is a mixture of one or more of L-carnitine, betaine, choline chloride, glycerophosphocholine, choline benzenesulfonate, choline citrate and choline dihydrogen citrate.

6. The adhesive according to claim 1, characterized in that The solvent is anhydrous ethanol and / or deionized water.

7. The adhesive according to claim 1, characterized in that The mass volume ratio of the total mass of the raw materials to the solvent is (0.5-5.0) g:1 mL.

8. A method for preparing the coatable paste-like biological tissue adhesive according to any one of claims 1 to 7, characterized in that: The lipoic acid or lipoic acid derivative, phenol structure compound and quaternary ammonium salt compound are dissolved in a solvent, placed in a vacuum oven for heating and polymerization treatment, and a paste-like biological tissue adhesive that can be applied is obtained.

9. The preparation method according to claim 8, characterized in that: The heating polymerization temperature is 70°C and the time is 1 to 48 hours.

10. A use of the coatable paste-like biological tissue adhesive according to any one of claims 1 to 7, characterized in that: Apply the adhesive directly to the surface of the adherend.